L'Antiquité est une fête - Lacroix, Audrey (B@lades, 2022)
L'Antiquité est une fête is a series of texts proposed by specialists in the sciences of antiquity to highlight the time and practices of the festival in the ancient worlds. Private parties or public festivals, how did the Ancients entertain themselves? According to which temporality, with whom, by which consumption? This collection is an invitation to (re)discover the many facets of ancient collective pleasures: circus games, Greek banquets, children's games, preparations for meals, wine, music, gifts, etc. Anxious to make the complexity of ancient history accessible to as many people as possible, the Revue des Études Anciennes proposes to promote and disseminate scientific knowledge in original ways so that as many people as possible can grasp it. This series is thus at the initiative of the Revue's scientific notebook, 'Actualités des Études Anciennes', which offers scientific and cultural news relating to Antiquity as a whole. It thus offers a new support to history and archaeology enthusiasts, students and teachers by providing resources and research results. Finally, it also aims to be a space for information and debate.